THE LINKAGES BETWEEN AGRICULTURAL INPUT AND FOOD PRODUCTION IN LEAST DEVELOPING COUNTRIES - Nur Marina Abdul Manap (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Food is among the basic human needs for social development. Sufficiency of food depends not only on domestic food production but also on food imports and food aid. However, all countries need to increase their food production to fulfil domestic sufficiency so they will not be too dependent on food imports and food aid. This paper examines the linkages between agriculture input and food production in the least developing countries. The data sets of the variables in this paper were obtained from FAOSTAT and the variables were considered throughout the analysis were food production index, fertilizers consumption, land irrigation, gross fixed capital formation, and employment in the agriculture sector. The static panel data was adopted using fixed effect and the findings of this study showed that fertilizer, land irrigation, and capital formation in the agriculture sector positively significantly give an impact to food production in the least developing countries. In accordance with the objectives of this study, land irrigation provides a huge impact on food production. The governments, in partnership with public and private institutions, need to work toward defining and implementing comprehensive strategies for irrigation development